Comparative Analysis Between PI Conventional and Cascade Control in Heater-PFR-Series - Dedy Kristanto; Yulius Deddy Hermawan (Dept. of Chemical Engineering, Diponegoro University, 2020)
The goals of this work are to compare and analyze the use of PI conventional and Cascade control configuration in heater-plug-flow-reactor-series (Heater-PFR-series) to produce benzene through the reaction of hydrodealkylation of toluene (HDA).The two control configurations were rigorously examined in UniSim dynamic simulation environment. The PI control parameters were tuned by using “autotuner” mode of UniSim. As shown in dynamic simulation study, the two control configurations with its tuning parameters gave the fast and stable responses. This study revealed that the Cascade control acted very well and its responses were better and faster than those in PI-conventional.Keywords: cascade control; dynamic simulation; PFR; PI conventional; UniSim